Dispersing agent as well as preparation method and application thereof

By using polymers containing -C-O- and -C-N-single bond groups on the main chain and rich in hydrocarbon groups, siloxane-containing segments and fatty segments as dispersants, the problems of uneven distribution and poor flexibility of electrode active materials in the electrode sheet are solved, and better dispersion of electrode materials and flexibility of electrode sheets are achieved, thereby improving the performance of the battery.

CN119708505APending Publication Date: 2025-03-28SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411570181.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The electrode active materials in the existing electrode sheets are unevenly distributed and have poor flexibility, which is prone to cracking, affecting the capacity and circulation performance of the battery.

Method used

A dispersant containing a specific polymer is used, the backbone of the polymer containing -C-O- and -C-N-single bond groups and grafted with side chains on the backbone, including at least one of hydrocarbon groups, siloxane-containing segment groups and fat-containing segment groups.

Benefits of technology

This dispersant can effectively improve the dispersion of the electrode active material in the slurry, reduce the cohesive energy of the electrode material layer, improve the flexibility and structural stability of the electrode sheet, and thereby improve the capacity and circulation performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121275780000041
    Figure BDA0005121275780000041
  • Figure BDA0005121275780000051
    Figure BDA0005121275780000051
  • Figure BDA0005121275780000062
    Figure BDA0005121275780000062
Patent Text Reader

Abstract

The invention discloses a dispersing agent as well as a preparation method and application thereof. The dispersing agent comprises a polymer, a main chain of the polymer contains at least one single-bond group of-C-O-and-C-N-, a side chain containing an internally rotatable single-bond group and / or an electrophilic group is grafted on the main chain, and the side chain is at least locally and symmetrically connected on the main chain of the polymer. The polymer contained in the dispersing agent is rich in groups capable of internally rotating and electrophilic groups, so that the polymer is endowed with good dispersing and softening effects. When the dispersing agent is used as an electrode slurry dispersing agent, cohesive energy of an electrode active material layer can be reduced, distribution uniformity of an electrode active material can be improved, an undesirable phenomenon of cracking of the electrode active material layer can be reduced, and flexibility and structural stability of the electrode active material layer can be improved, so that exertion and cycle performance of electrode capacity can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of batteries, and specifically relates to a dispersant and a preparation method and application thereof. Background Art

[0002] The pole piece is an important component of the battery. During the preparation process of the pole piece, the electrode active material is generally prepared into a slurry, and then an electrode active material layer is formed on the current collector. However, due to the characteristics of the electrode active material itself, such as high surface energy (especially nano-scale electrode materials), the electrode active material is easy to agglomerate and condense during slurrying, resulting in uneven prepared slurry and high viscosity of the discharge, thereby reducing the uniformity of the distribution of the electrode active material in the electrode active material layer and the quality of the film layer. In addition, when the pole piece is dried, the solvent evaporates and the stress is concentrated. The pole piece, especially the pole piece with thick coating to increase the energy density, is prone to cracking. In this way, these deficiencies of the pole piece directly affect the capacity and cycle performance of the battery.

[0003] In order to improve the dispersibility of the electrode active material in the slurry and reduce the cracking of the electrode piece, it is currently disclosed to add a dispersant or further add a softener when preparing the slurry. However, research has found that the existing dispersing effect is limited, resulting in the electrode active material in the slurry being still not ideally dispersed; although the additional softeners can alleviate the cracking of the electrode piece to a certain extent, it is still not ideal, especially as the thickness and surface density of the electrode piece increase, these softeners cannot effectively alleviate the cracking of the electrode piece. Summary of the invention

[0004] The purpose of the present application is to overcome the above-mentioned deficiencies of the prior art and to provide a dispersant and a preparation method thereof, so as to solve the technical problems of uneven distribution of electrode active materials contained in the existing pole pieces, poor pole piece flexibility, and easy cracking.

[0005] In order to achieve the above application purpose, the first aspect of the present application provides a dispersant. The dispersant of the present application includes a polymer, the main chain of the polymer contains at least one single bond group of -CO- and -CN-, and the main chain is grafted with a side chain, the side chain is at least partially symmetrically connected on the main chain of the polymer, and the side chain includes at least one group of a hydrocarbon group, a siloxane segment-containing group, and a fat segment-containing group.

[0006] The main chain of the polymer contained in the dispersant of the present application is rich in -O-groups and / or -CN-single-bond groups containing -N-groups, and the nitrogen atoms and oxygen atoms can form hydrogen bonds or generate intermolecular interactions with the electrode active materials, thereby giving the polymer good electronegativity and electrophilicity. When the side chains of the polymer include siloxane segment groups and aliphatic segment groups, these side chain groups also have good electrophilicity, and they can also form hydrogen bonds or generate intermolecular interactions with the electrode active materials. Therefore, the polymer can have a strong affinity with the electrode active material, can be effectively adsorbed on the surface of the electrode active material particles, play a role in buffering and hindering the direct contact of the electrode active material particles, thereby effectively reducing the agglomeration of the electrode active material particles, and when preparing the electrode slurry, the dispersant of the present application can play a good dispersing role, thereby improving the uniformity of the electrode slurry, thereby improving the quality of the electrode.

[0007] At the same time, since the main chain of the polymer is rich in -CO- groups and / or -CN- single bond groups, the single bonds of these -CO- groups and / or -CN- groups are prone to internal rotation, thereby giving the main chain of the polymer high flexibility. When the side chain in the polymer contains a siloxane segment group, it is rich in -Si-O- groups, and the -Si-O- groups have good flexibility and can reduce the surface tension of the polymer; when the side chain contains a fatty segment group, it is rich in -CC- groups with low internal rotation energy, and the -CC- groups are also prone to internal rotation, and can increase the number of conformations and improve the flexibility of the polymer; when the side chain contains a hydrocarbon group, it is rich in saturated single bonds, and is also prone to internal rotation, and can also play a role in regulating the overall polarity and hydrogen bonds of the polymer molecule, thereby improving and regulating the flexibility of the polymer. Moreover, the side chains are at least partially symmetrically connected on the main chain of the polymer. The symmetrical connection and the type of the side chain can enhance the flexibility of the polymer and effectively reduce the glass transition temperature of the polymer. Therefore, both the main chain and the side chain contained in the polymer can effectively give the polymer good flexibility, and the side chain is connected to the main chain, affecting each other's charge distribution and also playing a role in enhancing flexibility.

[0008] In a second aspect, the present application provides an electrode material. The electrode material of the embodiment of the present application comprises an electrode active material and the above-mentioned dispersant, wherein the electrode active material is a positive electrode active material or a negative electrode active material.

[0009] Since the electrode material of the present application contains the dispersant of the above-mentioned application, the slurry prepared by the electrode material of the present application has a high solid content and low viscosity, and the formed electrode material layer has good flexibility and structural stability, and the electrode material is evenly distributed, and a thick electrode material layer can also be formed.

[0010] In a third aspect, the present application provides a battery. The battery of the present application embodiment comprises a negative electrode sheet and a positive electrode sheet, wherein the electrode material layer of at least one of the negative electrode sheet and the positive electrode sheet comprises the dispersant of the present application.

[0011] At least one of the negative electrode and the positive electrode of the battery contains the dispersant of the present application. Therefore, the electrode material contained in the electrode material layer is evenly distributed with less agglomeration, and the electrode material layer has good flexibility, thereby effectively improving the quality and mechanical properties of the electrode, and improving the capacity and cycle performance of the electrode. DETAILED DESCRIPTION

[0012] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0013] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0014] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0015] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0016] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0017] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0018] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0019] With the rapid development of mobile electronic devices, electric vehicles and renewable energy, batteries, especially lithium-ion batteries, have been widely used as an energy storage device with high energy density and long life.

[0020] The pole piece is an important component of the battery. During the preparation process of the pole piece, the electrode active material is generally prepared into a slurry, and then an electrode active material layer is formed on the current collector. However, due to the characteristics of the electrode active material (especially the nano-scale electrode material), such as high surface energy, the electrode active material is easy to agglomerate and condense during slurrying, resulting in uneven prepared slurry and high viscosity of the discharge, thereby reducing the uniformity of the distribution of the electrode active material in the electrode active material layer and the quality of the film layer. In addition, when the pole piece is dried, the solvent evaporates and the stress is concentrated. The pole piece, especially the pole piece with thick coating to increase the energy density, is prone to cracking. In this way, these deficiencies of the pole piece directly affect the capacity and cycle performance of the battery.

[0021] In order to improve the dispersibility of electrode active materials in slurry and reduce the cracking of pole pieces, there are currently public methods of using fatty polyether phosphates, BYK-type dispersants, etc. as dispersants, or further adding monomethyl polyethylene glycol, ethylene carbonate EC, etc. as softeners. However, studies have found that the dispersing effect of dispersants such as fatty polyether phosphates and BYK-type dispersants is limited, resulting in unsatisfactory dispersion of electrode active materials in slurry and failure to reduce the cracking of pole pieces; although the additional softeners can alleviate the cracking of pole pieces to a certain extent, the effect of alleviating the cracking of pole pieces is still unsatisfactory, especially with the increase of pole piece thickness and surface density, these softeners cannot effectively alleviate the cracking of pole pieces, such as Y-shaped cracking, and the addition of softeners also reduces the capacity density of pole pieces.

[0022] Although there are public reports of using polymers as both dispersants and softeners, the polymer molecules contain a large number of aromatic rings and conjugated double bond rigid groups, and their softening effect is not ideal, which will still lead to cracking of the pole piece. In particular, as the thickness and surface density of the pole piece increase, the cracking of the pole piece becomes more obvious. For example, the current surface density of the negative electrode can only be 7.5-22 mg / cm 2 The positive electrode surface density is 19.48~38.96mg / cm 2 .

[0023] In order to effectively overcome the undesirable phenomena such as uneven distribution and easy cracking of the electrode active materials contained in the electrode piece, the embodiment of the present application provides a dispersant containing a polymer, which can make the polymer have good dispersing and softening effects at the same time through the selection of the polymer main chain and side chains.

[0024] [Dispersant]

[0025] In a first aspect, an embodiment of the present application provides a dispersant. The dispersant of the embodiment of the present application includes a polymer, the main chain of the polymer contains at least one single bond group of -CO- and -CN-, and a side chain is grafted on the main chain of the polymer; the side chain is at least partially symmetrically connected on the main chain of the polymer, and the side chain includes at least one of a hydrocarbon group, a siloxane-containing segment group, and a fat-containing segment group.

[0026] In the present application embodiment dispersant, polymer refers to an organic substance containing repeating units, and the main chain of the repeating unit at least constitutes a part of the main chain of the polymer or constitutes the skeleton structure of the polymer. Therefore, the main chain of the polymer contains at least one single-bonded group in -CO- and -CN-. It can be understood that the single-bonded group is arranged on the main chain of the repeating unit, and of course it can also be arranged on the side chain. When at least one single-bonded group containing -CO- and -CN- is arranged in the repeating unit, it can be that any single-bonded group containing -CO- and -CN- is arranged in the repeating unit, or it can be that the single-bonded group containing -CO- and -CN- is arranged in the repeating unit at the same time. The side chain is a branched group connected to the main chain of the polymer. The hydrocarbon group in the side chain refers to an organic group consisting of only two atoms of carbon (C) and hydrogen (H); a siloxane segment group refers to a group containing -Si-O-; a fat segment group refers to a group containing aliphatic hydrocarbon (also referred to as aliphatic hydrocarbon) in the molecular structure.

[0027] Since the main chain of the polymer contained in the dispersant of the embodiment of the present application contains at least one single-bond group in -CO- and -CN-, therefore, the main chain of the polymer is rich in -O- and / or -N- groups, giving the polymer good electronegativity and electrophilicity, and can form hydrogen bonds or generate intermolecular interactions with electrode active materials. At the same time, when the side chain contains a siloxane segment group and a fat segment group, these side chain groups also have good electrophilicity, and they can also form hydrogen bonds or generate intermolecular interactions with electrode active materials. Therefore, the polymer can produce a strong affinity with the electrode active material, can be effectively adsorbed on the surface of the electrode active material particles, play a role in buffering and hindering the direct contact of the electrode active material particles, thereby effectively reducing the agglomeration of the electrode active material particles, when preparing the electrode slurry, the dispersant of the embodiment of the present application can play a good dispersing role, thereby improving the uniformity of the electrode slurry, thereby improving the quality of the electrode.

[0028] At the same time, since the main chain of the polymer is rich in -CO- groups and / or -CN- single bond groups, the single bonds of these -CO- groups and / or -CN- groups are prone to internal rotation, thereby giving the main chain of the polymer high flexibility. When the side chain contains a siloxane segment group, it is rich in -Si-O- groups, and the -Si-O- groups have good flexibility and can reduce the surface tension of the polymer; when the side chain contains a fatty segment group, it is rich in -CC- groups with low internal rotation energy, and the -CC- groups are also prone to internal rotation, and can increase the number of conformations and improve the flexibility of the polymer; when the side chain contains a hydrocarbon group, it is rich in saturated single bonds, and is also prone to internal rotation, and can also play a role in regulating the overall polarity and hydrogen bonds of the polymer molecule, thereby improving and regulating the flexibility of the polymer. Moreover, the side chains are at least partially symmetrically connected on the main chain of the polymer. The symmetrical connection and the type of the side chain can enhance the flexibility of the polymer and effectively reduce the glass transition temperature of the polymer. Therefore, the main chain and side chain contained in the polymer can effectively give the polymer good flexibility, and the side chain is connected to the main chain, affecting each other's charge distribution, and can also play a role in flexibility enhancement. When the polymer is added to the electrode slurry, it can play the role of a softener while giving full play to the role of a dispersant, reducing the cohesive energy of the electrode active material layer, reducing the cracking phenomenon of the electrode active material layer, and improving the flexibility and structural stability of the electrode active material layer, thereby improving the performance of the electrode capacity and cycle performance.

[0029] The repeating units of polymers are:

[0030] A polymer generally contains more than one repeating unit. In this case, as mentioned above, it can be understood that at least one single-bond group containing -CO- and -CN- is arranged on the main chain of the repeating unit, but it may not be arranged on the main chain of the repeating unit. In the embodiment, it is desirable in the embodiment of the present application that at least one single-bond group containing -CO- and -CN- is arranged on the main chain of the repeating unit, so that the proportion of the single-bond groups contained in the polymer can be increased, thereby improving the dispersibility and flexibility of the polymer.

[0031] When at least one of the single-bond groups -CO- and -CN- is set in the repeating unit, it can be that any of the single-bond groups -CO- and -CN- is set in the repeating unit, or the single-bond groups -CO- and -CN- are set in the repeating unit at the same time. When both -CO- and -CN- single-bond groups are contained, the -CO- and -CN- can be connected to the main chains of different repeating units respectively. For example, when the repeating unit contains -CO-, the repeating unit can be but not limited to a polyether repeating unit; when the repeating unit contains -CN-, the repeating unit can be but not limited to an amide repeating unit (that is, a repeating unit containing -CO-N-). Of course, they can also be connected to the main chain of the same repeating unit.

[0032] In the embodiment, the polymer includes repeating units A and / or repeating units B of different molecular structural formulas. In this case, the polymer belongs to a block copolymer. Then in the block copolymer, the main chain of at least one of the repeating units A and the repeating units B contains at least one single bond group of the above-mentioned -CO- and the -CN-. In order to more intuitively understand the polymer (block copolymer) containing repeating units A and repeating units B, its general structural formula includes the following general structural formula I:

[0033]

[0034] In the general structural formula I, 20≤a1≤50; 0≤a2≤45, optionally 15≤a2≤45; 0≤a2≤50, optionally 20≤a3≤50. The a1, a2, a3 may represent the polymerization degree or content ratio of the repeating unit A and the repeating unit B in the polymer.

[0035] In the general structural formula I, R1, R2, R3, R4, R5, and R6 can independently include any group of H, hydrocarbon group, siloxane-containing segment, and fat-containing segment. When R1, R2, R3, R4, R5, and R6 are independently any group of hydrocarbon group, siloxane-containing segment, and fat-containing segment, the hydrocarbon group can be the hydrocarbon group in the above side chain, or other alkyl group; the siloxane-containing segment group can be the siloxane-containing segment group in the above side chain, or other siloxane-containing segment group; the fat-containing segment group can be the fat-containing segment group in the above side chain, or other siloxane-containing segment group. Among them, when at least one pair of groups among R1 and R2, R3 and R4, and R5 and R6 are simultaneously any group of hydrocarbon group, siloxane-containing segment, and fat-containing segment, as in the above side chain. When at least one pair of groups among R1 and R2, R3 and R4, R5 and R6 is simultaneously a hydrocarbon group, a siloxane-containing segment and a fat-containing segment, such as the above-mentioned side chain, the side chain is at least partially symmetrically connected on the main chain of the polymer. Thereby improving the flexibility of the polymer, the glass transition temperature of the polymer can be reduced at the same time. Of course, relatively more groups such as all groups among R1 and R2, R3 and R4, R5 and R6 are the above-mentioned side chains, or further, each pair of groups is the same (such as R1 is the same as R2, R3 is the same as R4, R5 is the same as R6), and being connected to the same atom is what the embodiment of the present application hopes, so that the content of the side chain in the polymer can be increased and the symmetry of the side chain on the main chain of the polymer can be improved, thereby improving the synergistic effect of the side chain on the flexibility and dispersibility of the polymer, and reducing the glass transition temperature of the polymer. As in the embodiment, when R1 and R2, R3 and R4, R5 and R6 are all hydrocarbon groups, siloxane-containing segments and aliphatic segments, such as the above-mentioned side chains, the polymer is a fishbone structure. The flexibility and dispersibility of the polymer with the fishbone structure are relatively excellent, and the glass transition temperature is relatively low.

[0036] In the general structural formula I, the repeating units A and B can be arranged randomly. For example, in the exemplary embodiment, the repeating units of the polymer can be arranged in an alternating pattern of -ABAB-, or in an arrangement of -AAB-, and of course in an arrangement of -BBA-.

[0037] In an embodiment, when the main chain of the repeating unit contained in the polymer contains -CO- and -CN- single bond groups, the molar ratio of the -CO- and the -CN- single bond groups is (1-1.8): 1, and optionally (1.11-1.3): 1. In the exemplary embodiment, it can be 1: 1, 1.11: 1, 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1, 1.6: 1, 1.7: 1, 1.8: 1. In this molar ratio range, the content of the -CO- single bond group is relatively high relative to the -CN- single bond group, thereby reducing the internal rotation energy of the polymer main chain, improving the internal rotation characteristics of the main chain, and thus improving the flexibility of the polymer.

[0038] In some embodiments, the polymer includes at least one of the repeating units shown in the following general structural formula I1, the repeating units shown in the following general structural formula I2, and the repeating units shown in the following general structural formula I3:

[0039]

[0040] Wherein, a11 in the general structural formula I1 may be: 20≤a11≤50, and in the exemplary embodiment, the a11 may be, but not limited to, 20, 25, 30, 35, 40, 45, 50. The a11 value in this range can adjust the main chain length of the repeating unit shown in the general structural formula I1, thereby adjusting the proportion of the polymer -CO- group, thereby improving the dispersing effect and softening effect of the polymer.

[0041] a12 in the general structural formula I1 can be: 1≤a12≤5. In the exemplary embodiment, a12 can be, but is not limited to, 1, 2, 3, 4, or 5. The value of a12 represents the number of carbon atoms in the carbon chain (main chain) in the repeating unit of the single general structural formula I1. For example, when a12 is 2, the carbon chain in the repeating unit of the single general structural formula I1 is -CC-. When a12 is 3, the carbon chain in the repeating unit of the single general structural formula I1 is -CCC-. The a12 value in this range can adjust the length of the carbon chain in the repeating unit of the single general structural formula I1, thereby improving the softening effect of the polymer.

[0042] R in the general structural formula Ⅰ1 11 , R 12 are independently any one of H, hydrocarbon, siloxane-containing segments and fat-containing segments. 11 , R 12 When all are H, it means that there is no side chain in the repeating unit shown in the general structural formula Ⅰ1; when R 11 , R 12 When they are not H at the same time, it means that the repeating unit shown in the general structural formula Ⅰ1 contains a side chain, or further, when R 11 , R 12are all side chains, so that the side chains are symmetrically connected in the repeating units shown in the general structural formula Ⅰ1, thereby increasing R 11 , R 12 It has a synergistic effect on the flexibility of the polymer and can further reduce the glass transition temperature of the polymer. This situation is relatively preferred in the embodiment of the present application. 11 , R 12 When at least one of the groups in is a side chain group other than hydrogen, then the R 11 , R 12 At least one of the groups in the R constitutes a side chain of the polymer, which includes at least one of a hydrocarbon group, a siloxane-containing segment group and a fat-containing segment group as described above. 11 , R 12 The content of the repeating unit shown in the general structural formula Ⅰ1 can be adjusted by the size of a11 and a12, thereby adjusting the R as a side chain. 11 , R 12 Play a role in dispersing and softening polymers.

[0043] a13 in the general structural formula I2 may be: 15≤a13≤45, optionally 15≤a13≤40, and in the exemplary embodiment, the a13 may be, but is not limited to, 15, 18, 20, 23, 25, 28, 30, 33, 35, 38, 40, 42, 45, etc. The a13 value in this range can adjust the main chain length of the repeating unit shown in the general structural formula I2, thereby adjusting the proportion of the polymer -CO-N- group, thereby improving the dispersion and softening effect of the polymer.

[0044] R in the general structural formula Ⅰ2 13 It can be any group of H, hydrocarbon group, siloxane-containing segment and aliphatic segment. 13 When R is H, it means that the repeating unit shown in the general structural formula Ⅰ2 does not contain a side chain; 13 When R is not H, it means that the repeating unit shown in the general structural formula Ⅰ2 contains a side chain, which is a relatively preferred embodiment of the present application. 13 When the side chain group is not hydrogen, the R 13 The side chain constituting the polymer includes at least one of a hydrocarbon group, a siloxane-containing segment group and a fat-containing segment group as described above. 13 The content of the repeating unit shown in the general structural formula I2 can be adjusted by the size of a13, thereby adjusting the R as a side chain. 13 Play a role in dispersing and softening polymers.

[0045] a14 in the general structural formula Ⅰ3 can be: 15≤a14≤40, and can be optionally 20≤a14≤30. In the exemplary embodiment, a14 can be but is not limited to 15, 18, 20, 23, 25, 28, 30, 33, 35, 38, 40.

[0046] The a14 or a15 value within this range can adjust the main chain length of the repeating unit shown in the general structural formula I3, thereby adjusting the proportion of -CO-N- groups in the polymer, thereby improving the dispersion and softening effects of the polymer.

[0047] a15 in the general structural formula I3 may be: 1≤a15≤8. In the exemplary embodiment, a15 may be, but is not limited to, 1, 2, 3, 4, 5, 6, 7, 8, etc. The value of a15 represents the number of carbon atoms in the carbon chain in the repeating unit of the single general structural formula I3. For example, when a15 is 1, the carbon chain in the repeating unit of the single general structural formula I3 is -C-. When a15 is 2, the carbon chain in the repeating unit of the single general structural formula I3 is -CC-. The a15 value in this range can also adjust the length of the carbon chain in the repeating unit of the single general structural formula I3, thereby improving the softening effect of the polymer.

[0048] R in the general structural formula Ⅰ3 14 , R 17 Each independently represents any group such as H, alkyl, etc.

[0049] R in the general structural formula Ⅰ3 15 , R 16 are independently any one of H, hydrocarbon, siloxane-containing segments and fat-containing segments. 15 , R 16 When all are H, it means that the repeating unit shown in the general structural formula Ⅰ3 does not contain a side chain; when R 15 , R 16 are not H at the same time, it means that the repeating unit represented by the general structural formula I3 contains a side chain, or further, R 15 , R 16 are all side chains, so that the side chains are symmetrically connected in the repeating units shown in the general structural formula Ⅰ3, thereby increasing R 15 , R 16 It has a synergistic effect on the flexibility of the polymer and can further reduce the glass transition temperature of the polymer. This situation is relatively preferred in the embodiment of the present application. 15 , R 16 When at least one of the groups in is a side chain group other than hydrogen, then the R 15 , R 16 At least one of the groups in the R constitutes a side chain of the polymer, which includes at least one of a hydrocarbon group, a siloxane-containing segment group and a fat-containing segment group as described above. 15 , R16 The content of the repeating unit shown in the general structural formula I3 can be adjusted by adjusting the size of a14 and a15, thereby adjusting the R as a side chain. 15 , R 16 Play a role in dispersing and softening polymers.

[0050] In addition, since the main chain of the polymer, especially the main chain of the repeating unit contained therein, contains a side chain, therefore, in the embodiment, the R contained in the repeating unit shown in the above general structural formula I1 is 11 With R 12 R in the repeating unit shown in the general structural formula Ⅰ2 13 Or R in the repeating unit shown in the general structural formula Ⅰ3 15 , R 16 They are not simultaneously H. Furthermore, the side chains are at least partially symmetrically linked in the main chain of the polymer.

[0051] R in the general structural formula Ⅰ3 x1 , R x2 Separately And 1≤b1≤8. These types of R x1 , R x2 It can serve to connect other repeating units, such as a connecting group connecting the repeating units shown in general structural formula Ⅰ1, and adjust the connection relationship and connection stability between the repeating units shown in general structural formula Ⅰ1 and the repeating units shown in general structural formula Ⅰ3, thereby improving the chemical stability of the polymer and the dispersing and softening effects it plays.

[0052] In some embodiments, when the polymer includes a repeating unit represented by the general structural formula I1 and a repeating unit represented by the general structural formula I3, the general structural formula of the above polymer includes the following general structural formula II:

[0053]

[0054] Wherein, a11 and a12 in the general structural formula II are respectively a11 and a12 in the repeating unit shown in the general structural formula Ⅰ1 above, and R 11 , R 12 The R in the repeating unit shown in the general structural formula Ⅰ1 above are respectively 11 , R 12 ; a11' may be 0≤a11'≤50, and may further be in the value range of a11, and may be the same as or different from a11; a12' may be 0≤a12'≤5, and may further be in the value range of a12, and may be the same as or different from a12; R 11’ , R 12’ Can be independently 11 or R 12 The group shown in 11 or R12 same or different; a14, a15 are respectively a14, a15 in the repeating unit shown in the general structural formula Ⅰ3 above, R 14 , R 17 The R in the repeating unit shown in the general structural formula Ⅰ3 above are respectively 14 , R 17 , R 15 , R 16 The R in the repeating unit shown in the general structural formula Ⅰ3 above are respectively 15 , R 16 , R x1 , R x2 The R in the repeating unit shown in the general structural formula Ⅰ3 above are respectively x1 , R x2 .

[0055] Based on the molecular structure shown in the general structural formula Ⅱ, it can be simplified to -Ⅰ1-Ⅰ3-Ⅰ 1’ -. Since the polymer represented by the general structural formula II contains the repeating unit represented by the general structural formula I1 and the repeating unit represented by the general structural formula I3, and at least one of the two repeating units contains the above-mentioned side chain, the polymer represented by the general structural formula II has good dispersing and softening effects at the same time.

[0056] Of course, based on the repeating units shown in the general structural formula I1, the repeating units shown in the general structural formula I2, and the repeating units shown in the general structural formula I3, the above polymers may also include but are not limited to polymers of the general structural formulas -I1-I2-I3-, -I1-I2-, and -I2-I3-. The main chains of the polymers shown in these general structural formulas are all rich in at least one single bond group of -CO- and -CN- and the above side chains, and all have good dispersing and softening effects.

[0057] In some embodiments, when the side chain contained in the polymer repeating unit of the above embodiments includes a hydrocarbon group, the hydrocarbon group can be a straight-chain alkane group including C1 to C8. In exemplary embodiments, the hydrocarbon group can be but is not limited to an alkyl group such as methyl, ethyl, or propyl.

[0058] The above hydrocarbon groups are rich in saturated single bonds, which are prone to internal rotation and can improve the flexibility of the polymer; and can also play a role in regulating the overall polarity and hydrogen bonds of the polymer molecules, thereby improving and regulating the dispersibility and flexibility of the polymer.

[0059] In some embodiments, when the side chain contained in the polymer repeating unit of each of the above embodiments includes a siloxane-containing segment group, the siloxane-containing segment group includes a group represented by the following structural formula C1:

[0060]

[0061] Wherein, c1 in the general structural formula C1 may be 1≤c1≤4;

[0062] In the general structural formula C1, R x3 , R x4 Separately And 1≤b2≤8. These types of R x3 , R x4 The connecting group can serve to connect the main chain of the polymer, such as the main chain of the repeating unit shown in the above-mentioned general structural formula Ⅰ1, the repeating unit shown in the general structural formula Ⅰ2, and the repeating unit shown in the general structural formula Ⅰ3, so as to improve the stability of the connection between the siloxane segment group and the polymer main chain, thereby improving the stability of the dispersion and softening effect of the polymer.

[0063] R in the general structural formula C1 y1 , R y2 As a substituent group of Si atom, R y1 , R y2 are independently any of an alkyl group and an alkenyl group. y1 , R y2 When they are independently alkyl, the alkyl may be an alkyl having no more than 6 carbon atoms, such as at least one of ethyl, propyl, isopropyl, and butyl. y1 , R y2 When they are independently alkenyl, the alkenyl may be an alkenyl having no more than 6 carbon atoms, such as at least one of ethenyl, propenyl, isopropenyl, butenyl and the like.

[0064] The above-mentioned siloxane chain segment groups are rich in -Si-O- groups, which have good flexibility and can reduce the surface tension of the polymer and improve its flexibility. y1 , R y2 The substituent group can adjust the charge distribution of the -Si-O- group, thereby further improving the flexibility and affinity of the -Si-O- group, thereby further improving the dispersibility and flexibility of the polymer.

[0065] In some embodiments, when the side chains contained in the polymer repeating units of the above embodiments include fat chain segment-containing groups, the fat chain segment-containing groups contain C2-C18 fat chain segments, which may optionally be C2-C12 fat chain segments, C2-C16 fat chain segments, C10-C18 fat chain segments, etc.

[0066] In some embodiments, when the side chain contained in the polymer repeating unit of each of the above embodiments includes a fatty segment group, the fatty segment group includes at least one of a fatty alcohol group and a fatty ether group. In the embodiment, the fatty alcohol group includes a group shown in the following structural formula C2:

[0067]

[0068] Among them, in the general structural formula C2 A fatty chain is formed, and c2 can be 2≤c2≤16, R y3 , R y4 are independently any one of H, alkane, ester or silane, wherein the alkane, ester or silane may be a common group.

[0069] In the embodiment, the fatty ether group includes a group represented by the following structural formula C3:

[0070]

[0071] Among them, in the general structural formula C3 A fatty chain is formed, and c3 can be 2≤c3≤12, and c4 can be 2≤c4≤12; R y5 , R y6 , R y7 , R y8 Each is independently any one of H, an alkane group, an ester group or a silane group.

[0072] The above-mentioned fat-containing chain segment groups are all rich in -CC- groups with low internal rotation energy. The -CC- groups are also easy to rotate internally, and can increase the number of conformations and improve the flexibility of the polymer; at the same time, these fat-containing chain segment groups can reduce the strong steric hindrance caused by the bulky side chains, giving the polymer the effect of a plasticizer.

[0073] Functional end groups contained in the polymer:

[0074] In some embodiments, the main chain of the polymer in each of the above embodiments contains a functional end group. Wherein, the end group refers to any end position connected to the main chain of the polymer, or the relative end positions of the main chain. The end of the main chain of the polymer can be the terminal position of the main chain.

[0075] In some embodiments, when both opposite ends of the main chain of the polymer contain the functional end group, the general structural formula of the above polymer containing the functional end group can be as shown in the following III:

[0076]

[0077] Among them, R in general formula III d1 , R d2 are independently functional end groups.

[0078] In the embodiment, the functional end groups such as R d1 , R d2It includes at least one of a nitrogen (N)-containing group, a phosphorus (P)-containing group, and -C(X)-.

[0079] In an embodiment, when the functional end group contains a nitrogen (N)-containing group, the nitrogen (N)-containing group includes at least one of -NH2 and cyano (-C≡N).

[0080] In the embodiment, when the functional end group contains a phosphorus (P)-containing group, the phosphorus (P)-containing group includes but is not limited to a phosphonic acid group (—H 2 PO 3 ).

[0081] In the embodiment, when the functional end group contains a -C(X)- group, X in -C(X)- is a halogen substituent, such as at least one of F, Cl, Br, and I.

[0082] In the exemplary embodiment, R in the above general formula III d1 , R d2 It can be -NH2, -P, such as R d1 -NH2, R d2 It is -H2PO3.

[0083] At least some of the functional end groups mentioned above have strong polarity, such as nitrogen (N) groups, -C(X)-, etc., which can have strong compatibility with solvents, thereby improving the solubility or dispersibility of the polymer in the solvent. In this way, when the polymers of the above embodiments are added to the electrode slurry, the solubility and dispersibility of the polymer in the slurry can be improved, thereby improving the quality and flexibility of the electrode. At the same time, at least some of the functional end groups mentioned above can play the role of anchoring groups, such as phosphorus (P) groups, which have wettability and can have strong binding force with the granular material, thereby enhancing the binding force between the polymer and the granular material, and improving the dispersion uniformity and stability of the granular material. In this way, when the polymers of the above embodiments are added to the electrode slurry, the binding force between the polymer in the slurry and the electrode active material can be improved, thereby improving the dispersion uniformity and stability of the electrode active material in the slurry.

[0084] In addition, a11, a12, a14, a15, a11', and a12' in the general formula III are the same as a11, a12, a14, a15, a11', and a12' in the general formula II above, respectively. 11 , R 12 , R 14 , R 15 , R 16 , R 17 As shown in the above general structural formula II, 11 , R 12 , R 14 , R 15 , R 16 , R 17, R x1 , R x2 As shown in the above general structural formula II, x1 , R x2 .

[0085] Based on the types of repeating units and functional end groups contained in the polymers of the above embodiments, the polymers contained in the dispersants of the embodiments of the present application may be polymers represented by structural formulas (1) to (6) in Embodiments A1 to A6.

[0086] Since the polymers in the above embodiments contain the polyether repeating units and amide repeating units described above, the polyether repeating units and amide repeating units do not contain rigid groups such as aromatic groups and conjugated double bonds, or the content of rigid groups such as aromatic groups and conjugated double bonds can be controlled to be very low, so that the polymer does not contain rigid groups or contains very low rigid groups, thereby improving the flexibility of the polymer.

[0087] Furthermore, the dispersion and softening effect of the polymer can be adjusted and improved by adjusting the ratio of the polyether repeating unit and the amide repeating unit in the above polymer and the main chain length of each repeating unit. In some embodiments, the weight average molecular weight of the polymer in each embodiment above is 200 to 6000, and can be selected as 200 to 4000. The polymer with a molecular weight in this range has a relatively large number of conformations and a relatively high single bond content, which makes the flexibility of the polymer relatively better, and at the same time has a relatively high electrophilicity, which improves the dispersion effect of the polymer.

[0088] In addition, in some embodiments, the dispersants of the above embodiments may contain other additives in addition to the above polymers, such as functional additives that can enhance the function of the above polymers, or functional additives that can play a synergistic role in dispersing and softening the above polymers. Of course, the dispersants of the above embodiments may also contain only the above polymers. In the embodiments, these other additives may be additives suitable for electrode slurry applications.

[0089] Secondly, since the dispersants in the above embodiments contain the above polymers, and the polymers have good softening effects in addition to good dispersing effects, the above dispersants or polymers can be used as softeners and added to the electrode slurry to improve the mechanical properties of the electrode active material layer and improve its flexibility, thereby improving the structural stability and cycle performance of the electrode.

[0090] [Preparation method of dispersant]

[0091] In a second aspect, the present invention also provides a method for preparing the above dispersant. The method for preparing the dispersant in the present invention includes the method for preparing the above polymer, and the method for preparing the polymer includes the following steps:

[0092] The organic matter containing the repeating unit is subjected to addition polymerization to generate the above copolymer.

[0093] In the preparation method of the dispersant of the embodiment of the present application, the repeating unit refers to the repeating unit contained in the above polymer, and the main chain of the organic matter contains at least one single bond group of -CO- and -CN-. In addition, the main chain of some organic matters is connected with a side chain, which is also the side chain contained in the repeating unit in the above polymer, including at least one of a hydrocarbon group, a siloxane-containing segment group and a fat-containing segment group.

[0094] Therefore, in the preparation method of the dispersant of the embodiment of the present application, an organic substance including a main chain containing at least one single-bond group in -CO- and -CN- is subjected to addition polymerization, and the main chain of the generated polymer contains at least one single-bond group in -CO- and -CN-, and contains a side chain, and the side chain is at least partially symmetrically connected on the main chain. In this way, as described in the above polymer, the generated polymer is rich in internally rotating groups, and does not contain rigid groups such as aromatic groups, conjugated double bonds, or the content of rigid groups such as aromatic groups, conjugated double bonds can be controlled to be very low; at the same time, it is rich in electrophilic groups, thereby giving the polymer a good softening effect and good dispersibility. When the prepared dispersant is added to the electrode slurry, the polymer contained in the dispersant can play the role of a softener while giving full play to the role of the dispersant, reducing the cohesive energy of the electrode active material layer, reducing the cracking phenomenon of the electrode active material layer, and improving the flexibility and structural stability of the electrode active material layer, thereby improving the performance and cycle performance of the electrode capacity.

[0095] In some embodiments, the organic matter includes a first organic matter and a second organic matter that can undergo addition polymerization; in this case, the side chains contained in the first organic matter are at least partially symmetrically connected on the main chain of the repeating unit contained in the first organic matter, or / and the side chains contained in the second organic matter are at least partially symmetrically connected on the main chain of the repeating unit contained in the second organic matter. That is, the side chains contained in the first organic matter are at least partially symmetrically connected in the first organic matter, or the side chains contained in the second organic matter are at least partially symmetrically connected in the second organic matter, or the side chains contained in the first organic matter and the side chains contained in the second organic matter are at least partially symmetrically connected. At the same time, the main chain of the repeating unit contained in the first organic matter and / or the repeating unit contained in the second organic matter contains at least one single bond group of -CO-, -CN-.

[0096] Based on the structure of the first organic compound and the second organic compound, in the embodiment, the main chain of the repeating unit in the first organic compound contains a -CO- group, so the first organic compound contains a polyether repeating unit; the main chain of the repeating unit in the second organic compound contains a -CN- group, such as in the embodiment, the second organic compound may contain an amide repeating unit (the main chain contains -CO-N-). At this time, the repeating unit in the first organic compound may be a repeating unit shown in the general structural formula Ⅰ1 contained in the above polymer, and the repeating unit in the second organic compound may be a repeating unit shown in the general structural formula Ⅰ2 contained in the above polymer, and a repeating unit shown in the general structural formula Ⅰ3.

[0097] The first organic compound and the second organic compound of the above structure are subjected to addition polymerization, and the main chain of the generated polymer repeating unit, such as the polyether repeating unit and the amide repeating unit, is rich in -CO-groups, at least one single bond group among -CN-, and at least partially symmetrical side chains. In this way, as described in the above polymer, the polymer is rich in internal rotation groups and electrophilic groups, thereby giving the polymer a good softening effect and good dispersibility.

[0098] In some embodiments, when the organic matter includes the first organic matter containing polyether repeating units, the polyether repeating units contained in the first organic matter may be the repeating units shown in the general structural formula Ⅰ1 in the above polymer. Therefore, the first organic matter not only contains polyether repeating units, but also may further contain the side chains described above.

[0099] In an embodiment, the first organic matter can be formed by polymerization of a monomer including a polyether repeating unit. When the first organic matter contains a side chain, the main chain compound of the polyether repeating unit can be subjected to an addition reaction or an etherification reaction with a compound containing a side chain, and the side chain can be grafted on the main chain of the main chain compound of the polyether repeating unit. As in the exemplary embodiment, polyethylene glycol (PEG) can be subjected to an addition reaction with a compound containing a side chain under the action of a catalyst to generate a polyethylene glycol-side chain compound. Among them, the catalyst can be selected according to the type of compound containing a side chain. In the exemplary embodiment, the catalyst can be, but is not limited to, diphenyl phosphate. In the exemplary embodiment, PEG can include at least one of PEG-200, PEG-4000, PEG-6000 and PEG-20000. In the exemplary embodiment, the compound containing a side chain can be, but is not limited to, an alkyl lactone, which can include at least one of caprolactone, valerolactone, and other fatty substituted lactones.

[0100] In some embodiments, when the organic matter includes the second organic matter, the repeating unit contained in the second organic matter may be at least one of the repeating units shown in the general structural formula I2 and the repeating units shown in the general structural formula I3 in the above polymer. Therefore, the second organic matter not only contains an amide repeating unit, but also may further contain the side chain described above.

[0101] In an embodiment, the second organic compound can be formed by polymerization of a monomer including an amide repeating unit. When the second organic compound contains a side chain, the main chain compound of the amide repeating unit can be subjected to a nucleophilic substitution reaction with a compound containing a side chain, and the side chain can be grafted onto the main chain of the main chain compound of the amide repeating unit. As in the exemplary embodiment, the amide can be subjected to a nucleophilic substitution reaction with a compound containing a side chain to generate a compound of a polyethylene glycol-side chain. Wherein, a catalyst can be added to the nucleophilic substitution reaction, and the catalyst can be selected according to the type of compound containing a side chain, such as when the compound of the side chain is a halide, in the exemplary embodiment, the catalyst can be but not limited to NaH. In the exemplary embodiment, the halide can be but not limited to a brominated alkyl compound, which can include at least one of 1-bromotridecane, 1-bromoheptafluorooctane, 2-octyldodecyl bromide and brominated hexadecane.

[0102] In some embodiments, when the polymer contains a functional end group, the above-mentioned organic matter, such as at least one of the above-mentioned first organic matter and the second organic matter, may contain a functional end group. According to the type of the functional end group, a suitable method can be selected to synthesize an organic matter containing a functional end group, such as synthesizing the first organic matter and the second organic matter containing a functional end group respectively. As in the exemplary embodiment, PEG is reacted with thionyl bromide (SOBr2) in toluene and an organic amine to obtain PEG-Br, which is then placed in ethanol, ammonia is introduced, and the reaction obtains amino-terminated polyethylene glycol PEG-NH2. Finally, according to the above-mentioned addition reaction, the amino-terminated polyethylene glycol PEG-NH2 is subjected to an addition reaction with a compound containing a side chain, and the side chain is grafted on the main chain of the amino-terminated polyethylene glycol PEG-NH2. In the exemplary embodiment, the organic amine may include at least one of triethylamine, ethylenediamine, diethylamine, diethanolamine, and isopropanolamine.

[0103] In another exemplary embodiment, PEG can be mixed with a phosphorylation agent to obtain PEG-P, and finally, according to the above addition reaction, the amino-terminated polyethylene glycol PEG-P is subjected to an addition reaction with a compound containing a side chain, and the side chain is grafted onto the main chain of the amino-terminated polyethylene glycol PEG-NH2. Or PEG-P is subjected to an etherification reaction with a siloxane agent, and the side chain containing a siloxane segment group is grafted onto the main chain of the P-terminated polyethylene glycol PEG-P. In the exemplary embodiment, the phosphorylation agent can include at least one of phosphorus pentoxide, pyrophosphoric acid, phosphorus trichloride, and phosphoric acid, and the siloxane agent can include at least one of dimethyl-3-hydroxypropylmethylsiloxane, pentamethyldisiloxane, octaphenylcyclotetrasiloxane, 1,2-bis(triethoxysilyl)ethane, hexamethyldisiloxane, and tetraethoxysilane; the amide includes at least one of caproamide, acrylamide, malonamide, sebacamide, lauramide, linoleamide, and N-formylethylamide.

[0104] In some embodiments, when the organic matter contains the above-mentioned first organic matter and second organic matter, the first organic matter and the second organic matter can be added according to the molar ratio of -CO- and -CN- contained in the above polymer, such as controlling the mixing ratio of the first organic matter and the second organic matter so that the molar ratio of -CO- and -CN- in the generated polymer is (1 to 1.8):1.

[0105] In some embodiments, the addition polymerization reaction may be an oxygen Michael addition polymerization reaction, and in this case, the organic matter, such as the addition polymerization reaction system constructed by the reaction raw materials containing the first organic matter and the second organic matter, should satisfy the oxygen Michael addition polymerization reaction. For example, a reaction solvent for the composite oxygen Michael addition polymerization reaction may be selected, or a catalyst may be further added to accelerate the rate of the addition polymerization reaction, reduce side reactions, and increase the yield of the target polymer.

[0106] In an embodiment, the solvent for the addition polymerization reaction may include at least one of toluene, ether, cyclohexane, N,N-dimethylformamide, dimethyl sulfoxide, etc. These solvents can effectively improve the solubility of each raw material and reduce the generation of side reactions.

[0107] In the embodiment, when a catalyst is added to the addition polymerization reaction, the catalyst may include at least one of phosphazene base (t-BuP2), sodium ethoxide, potassium fluoride, nitrogen heterocyclic carbene, benzidine, etc. These types of catalysts can further increase the rate of the addition polymerization reaction, reduce side reactions, and increase the yield of the target polymer.

[0108] [Electrode materials]

[0109] In a third aspect, the present invention provides an electrode material. The electrode material of the present invention comprises an electrode active material and the dispersant of the above-mentioned present invention.

[0110] In the electrode material of the embodiment of the present application, the electrode active material contained therein may be a positive electrode active material or a negative electrode active material. The dispersant contained therein may form a physical mixture with the electrode active material, or may be provided separately.

[0111] Since the electrode material of the present application contains the dispersant of the embodiment of the present application, when the electrode material of the embodiment of the present application is prepared into a slurry, the dispersant contained therein can give full play to the role of the dispersant and the role of the flexibilizer, and can contact with the electrode active material particles and alleviate the agglomeration of the electrode active material particles, thereby reducing the viscosity of the slurry and improving the dispersibility and solid content of the slurry. When the electrode slurry forms an electrode material layer, it can significantly improve the uniformity of the thickness of the electrode material layer and the uniformity of the distribution of the electrode active material, and at the same time can significantly reduce the internal stress of the electrode material layer and improve its flexibility, thereby significantly improving the structural stability of the electrode sheet. In addition, the thickness of the electrode material layer can also be increased.

[0112] In the embodiments, when the electrode active material is a positive electrode active material, the positive electrode active material may be the positive electrode active material described in the battery below; when the electrode active material is a negative electrode active material, the negative electrode active material may be the negative electrode active material described in the battery below.

[0113] In the embodiment, in the electrode material, the mass ratio of the electrode active material to the dispersant can be such that after the electrode active material is prepared into an electrode material layer, the dispersant accounts for 0.05% to 0.2% of the mass of the electrode active material. This mass ratio range of the two can give full play to the above-mentioned role of the dispersant and increase the capacity of the electrode material to form a pole piece.

[0114] [Battery]

[0115] In a fourth aspect, an embodiment of the present application provides a battery. Specifically, the battery includes a positive electrode sheet, a negative electrode sheet and an electrolyte. Among them, the electrolyte can be a solid electrolyte, in which case, a diaphragm may not be provided in the battery. When the electrolyte is dispersed in the electrolyte, at this time, the battery also includes a diaphragm, and the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet to form an electrode assembly, and the electrode assembly is encapsulated in the cavity of the battery housing, and the electrolyte is injected into the cavity of the battery housing, and the electrode assembly is infiltrated. In addition, the positive electrode sheet contained in the battery of the embodiment of the present application includes a current collector and a positive electrode active material layer bonded to the surface of the current collector. In some embodiments, the negative electrode sheet may also include a current collector and a negative electrode active material layer bonded to the surface of the current collector. Of course, the negative electrode sheet may also be a metal negative electrode sheet.

[0116] In the battery of the embodiment of the present application, the electrode material layer of at least one of the negative electrode sheet and the positive electrode sheet includes the dispersant of the embodiment of the present application. In this way, the electrode material in the electrode material layer contained in the negative electrode sheet and the positive electrode sheet containing the dispersant is evenly distributed with little agglomeration, and the electrode material layer has good flexibility, thereby effectively improving the quality and mechanical properties of the electrode sheet, and improving the capacity and cycle performance of the electrode sheet.

[0117] In the embodiment, the dispersant contained in the electrode material layer of at least one of the negative electrode sheet and the positive electrode sheet accounts for 0.05% to 0.2% of the mass of the electrode active material. The dispersant in this mass content range can effectively improve the uniform dispersion of the electrode material in the electrode material layer, improve the capacity of the electrode active material, and at the same time improve the compaction density of the electrode material layer. For example, according to testing, the surface density of the electrode material layer on a single side of the electrode sheet can reach 42 to 51 mg / cm 2 . And it can further improve the mechanical properties of the pole piece, such as improving the flexibility of the pole piece, thereby improving the cycle performance of the pole piece.

[0118] Taking the positive electrode as an example, the positive electrode sheet of the battery includes a positive electrode active material, which may include one or more of a phosphate positive electrode active material, a binary positive electrode active material, and a ternary positive electrode active material. In a specific embodiment, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium fluorinated vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0119] In the embodiment, the positive electrode material layer in the positive electrode sheet of the battery includes not only the positive electrode active material but also the above-mentioned dispersant, and also includes components such as a binder and a conductive agent.

[0120] In the embodiment, the content of the binder contained in the positive electrode material layer in the positive electrode sheet can be 1wt% to 4wt%. In the exemplary embodiment, the content of the binder can be 1wt%, 2wt%, 3wt%, 4wt% and other typical but non-limiting contents. In the specific embodiment, the binder includes one or more of polyvinylidene fluoride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives.

[0121] In the embodiment, the content of the conductive agent contained in the positive electrode material layer in the positive electrode can be 1wt% to 5wt%. In the exemplary embodiment, the content of the conductive agent can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt% and other typical but non-limiting contents. In a specific embodiment, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes.

[0122] In the embodiment, the positive electrode current collector in the positive electrode sheet can be but is not limited to any one of copper foil and aluminum foil.

[0123] In the embodiment, the preparation process of the positive electrode sheet can be: the positive electrode active material, the above-mentioned dispersant, the conductive agent and the binder are mixed in proportion and added to the solvent to prepare the positive electrode slurry, the positive electrode slurry is coated on the current collector, and the positive electrode sheet is prepared through the steps of drying, rolling, die cutting and the like.

[0124] In addition, the battery in the embodiment of the present application can be a lithium-ion battery or a sodium-ion battery, etc.

[0125] The dispersant and preparation method thereof, battery, etc. of the present application are illustrated by multiple specific embodiments below.

[0126] 1. Dispersant and preparation method thereof:

[0127] Embodiment A1:

[0128] This embodiment provides a dispersant and a preparation method thereof. The dispersant includes a polymer represented by the following structural formula (1):

[0129]

[0130] The preparation method of the dispersant comprises the following steps:

[0131] S1: Add 10g PEG-200 and 10.5g thionyl bromide to 200mL anhydrous toluene, then add an appropriate amount of triethylamine, stir at room temperature for 24h, pour into ice ether for precipitation after the reaction, filter and dry. Take the dried product and add it to a mixture of 200mL anhydrous ethanol and ammonia water, stir at 80℃ for 24h to obtain PEG-NH2;

[0132] S2: Take 3g of PEG-NH2 prepared in step S1, add 1.2g of diphenyl phosphate, place in a 100mL flask containing 50mL of anhydrous toluene, and remove trace moisture by azeotropic distillation; add 1.5g of δ-valerolactone and 3g of lauryl alcohol, and stir for 4h under a nitrogen atmosphere at 50℃; after the reaction, pour the solution into cooled ether, store at -20℃ overnight, and precipitate a polymer; the obtained precipitate is washed 3 times with cold ether, and dried to obtain the ether ester NA-R1 shown in the following structural formula:

[0133]

[0134] S3: Take another 6g of PEG-200 and add it to 80mL of phosphorous acid solution at room temperature, slowly add 4.2g of P2O5 in batches, raise the temperature to 100°C, and continue stirring for 3h; collect the insoluble matter by filtration, add 5g of dimethyl-3-hydroxypropyl methylsiloxane, pour them into 150mL of anhydrous toluene, and react at 80°C for 5h under nitrogen protection with chloroplatinic acid as the catalyzer, remove low-boiling substances by vacuum decompression, and collect the ether siloxane PA-R3 shown in the following structural formula after cooling:

[0135]

[0136] S4: 3.75 g of sebacic acid amide and 8.4 g of 1-bromotridecane were added to anhydrous dimethyl sulfoxide, and 0.2 g of NaH powder was added as a catalyst. During the process, high-purity nitrogen was passed through to obtain B-R2 with the following structural formula:

[0137]

[0138] S5: Mix the obtained NA-R1, B-R2, and PA-R3, and add 2 wt% of t-BuP2 catalyst relative to the total mass, stir in toluene at room temperature for 12 h, add dilute hydrochloric acid to terminate the reaction, and precipitate in ethyl acetate. After drying, obtain the target polymer shown in the above structural formula (1).

[0139] Embodiment A2:

[0140] This embodiment provides a dispersant and a preparation method thereof. The dispersant includes a polymer represented by the following structural formula (2):

[0141]

[0142] The preparation method of the dispersant is synthesized by referring to the preparation method of the polymer represented by structural formula (1) in Example A1, except that step S4 is not provided and B-R2 is not added in step S5.

[0143] Example A3

[0144] This embodiment provides a dispersant and a preparation method thereof. The dispersant includes a polymer represented by the following structural formula (3):

[0145]

[0146] The preparation method of the dispersant is synthesized by referring to the preparation method of the polymer represented by structural formula (1) in Example A1, except that the ether ester NA-R1 prepared by steps S1 and S2 in this example has the following structure, and the polymerization degree of the polyether repeating unit containing ether group is 20, and the ether ester NA-R3 prepared by step S3 has the following structure, and the polymerization degree of the polyether repeating unit containing ether group is 20:

[0147]

[0148] Example A4

[0149] This embodiment provides a dispersant and a preparation method thereof. The dispersant includes a polymer represented by the following structural formula (4):

[0150]

[0151] The preparation method of the dispersant is synthesized by referring to the preparation method of the polymer represented by structural formula (1) in Example A1, except that the ether ester NA-R1 prepared by steps S1 and S2 in this example has the following structure, and the polymerization degree of the polyether repeating unit containing ether group is 30, and the ether ester NA-R3 prepared by step S3 has the following structure, and the polymerization degree of the polyether repeating unit containing ether group is 30:

[0152]

[0153] Example A5

[0154] This embodiment provides a dispersant and a preparation method thereof. The dispersant includes a polymer represented by the following structural formula (5):

[0155]

[0156] The preparation method of the dispersant is synthesized by referring to the preparation method of the polymer represented by structural formula (1) in Example A1, except that the siloxane side chains contained in the ether siloxane PA-R3 in step S3 of this example are not connected to the same carbon atom, resulting in asymmetric siloxane side chains.

[0157] Embodiment A6:

[0158] A mixed compound of a polymer (61) containing a symmetrical side group of -CO- and another polymer (62) containing a symmetrical side group of -CN- [not synthesized, simply blended]

[0159]

[0160] Comparative Example A1

[0161] This embodiment provides a dispersant and a preparation method thereof. The dispersant includes a polymer represented by the following structural formula (7):

[0162]

[0163] The preparation method of the dispersant comprises the following steps:

[0164] S1: Add 10g PEG-200 and 10.5g thionyl bromide to 200mL anhydrous toluene, then add an appropriate amount of triethylamine, stir at room temperature for 24h, pour into ice ether for precipitation after the reaction, filter and dry. Take the dried product and add it to a mixture of 200mL anhydrous ethanol and ammonia water, stir at 80℃ for 24h to obtain PEG-NH2;

[0165] S2: Take 3g of PEG-NH2 prepared in step S1, add 1.2g of diphenyl phosphate, place in a 100mL flask containing 50mL of anhydrous toluene, and remove trace moisture by azeotropic distillation; add 1.5g of δ-valerolactone and 5.2g of benzoic acid, and stir for 4h under a nitrogen atmosphere at 50℃; after the reaction, pour the solution into cooled ether, store at -20℃ overnight, and precipitate a polymer; the obtained precipitate is washed 3 times with cold ether, and dried to obtain the ether ester NA-R1' shown in the following structural formula:

[0166]

[0167] S3: Take another 6g of PEG-200 and add it to 80mL of phosphorous acid solution at room temperature, slowly add 4.2g of P2O5 in batches, raise the temperature to 100°C, and continue stirring for 3h; collect the insoluble matter by filtration, add 5g of cyanogen bromide and 0.2g of aluminum chloride, pour them into 150mL of anhydrous toluene, react at 80°C for 5h under nitrogen protection, remove low-boiling substances by vacuuming and reducing pressure, and collect the ether siloxane PA-R3' shown in the following structural formula after cooling:

[0168]

[0169] S4: 3.75 g of sebacic acid amide, 4.3 g of dichloroethane and 5.6 g of concentrated nitric acid were mixed and stirred, and high-purity nitrogen was passed through to obtain B-R2' shown in the following structural formula:

[0170]

[0171] S5: Mix the obtained NA-R1', B-R2', and PA-R3', and add 2 wt% of t-BuP2 catalyst relative to the total mass, stir in toluene at room temperature for 12 hours, add dilute hydrochloric acid to terminate the reaction, and precipitate in ethyl acetate, and after drying, obtain the target polymer represented by the above structural formula (1)

[0172] Comparative Example A2

[0173] This comparative example provides a dispersant and a preparation method thereof. The dispersant includes a polymer represented by the following structural formula (8), which is different from the polymer represented by the structural formula (1) in Example A1 in that each side chain is not connected to the same carbon atom, that is, the side chains are asymmetrically connected to the main chain of the polymer:

[0174]

[0175] The preparation method of the dispersant is synthesized by referring to the preparation method of the polymer represented by structural formula (1) in Example A1, except that the -(CH2)-OH side chains contained in the ether ester NA-R1 structure prepared by steps S1 and S2 in this example are not connected to the same carbon atom, resulting in asymmetric -(CH2)-OH side chains; and the siloxane side chains contained in the ether siloxane PA-R3 in step S3 are not connected to the same carbon atom, resulting in asymmetric siloxane side chains.

[0176] Comparative Example A3

[0177] This comparative example provides a dispersant, which is an ABS copolymer represented by the following structural formula (9):

[0178]

[0179] 2. Battery Example:

[0180] Example B1 to Example B6 and Comparative Example B1 and Comparative Example B3:

[0181] Embodiments B1 to B6 and Comparative Examples B1 and B3 each provide a lithium ion battery.

[0182] The lithium-ion batteries are as follows:

[0183] 1) Positive electrode:

[0184] The positive electrode active material lithium iron phosphate, the conductive agent SP, the binder polyvinylidene fluoride PVDF, and the softening dispersant are fully stirred and mixed in an N-methylpyrrolidone solvent system in a mass ratio of 97:2:1:0.1 to form a positive electrode slurry, which is coated on an Al foil by extrusion coating or transfer coating, dried, and cold pressed to obtain a positive electrode sheet, and the thickness of the positive electrode film layer thereon is 215 μm; wherein, the softening dispersant contained in the positive electrode sheet in Example B1 is the dispersant in Example A1, and the softening dispersant contained in the positive electrode sheet in Example B2 is the dispersant in Example A2. Similarly, by analogy, the softening dispersant contained in the positive electrode sheet in Comparative Example B3 is the dispersant in Comparative Example A3.

[0185] 2) Negative electrode:

[0186] The negative electrode active material, the conductive agent and the binder having a mass ratio of 93.4:4:2.6 are mixed evenly in deionized water to form a negative electrode slurry, and the negative electrode slurry is coated on the current collector copper foil, and after drying-rolling-second drying process, a negative electrode sheet is formed, and the designed nominal capacity is 2Ah;

[0187] The negative electrode active material is artificial graphite, the conductive agent is conductive carbon black, and the binder is sodium carboxymethyl cellulose and / or styrene-butadiene rubber.

[0188] 3) Diaphragm: Use polyethylene (PE) diaphragm.

[0189] 4) Electrolyte: The electrolyte is a 1 mol / L LiPF6 solution, and the solvent is composed of EC (ethylene carbonate) and DEC (diethyl carbonate) in a volume ratio of 1:1.

[0190] 5) Assembly of lithium-ion batteries:

[0191] The positive electrode sheet, negative electrode sheet, electrolyte and separator are assembled into the lithium ion batteries of Examples B1 to B7 and Comparative Examples B1 to B2 respectively according to the requirements for lithium ion battery assembly. Among them, the active material layer of the positive electrode sheet of the lithium ion battery in Example B1 contains the dispersant in Example A1, and the active material layer of the positive electrode sheet of the lithium ion battery in Example B2 contains the dispersant in Example A3. Similarly, the softening dispersant contained in the positive electrode sheet in Comparative Example B2 is the dispersant in Comparative Example A2.

[0192] 3. The lithium ion batteries and the positive electrodes contained therein provided in Examples B1 to B7 and the comparative examples were subjected to the following performance tests:

[0193] Positive electrode flexibility test method: First, according to the standard of "QB / T 1060-2012 Softness Tester", the softness tester was installed and calibrated. The softness tester model used was ZRD-T1 produced by Saicheng Instruments; then according to the standard method of "GB / T8942-2016 Determination of Paper Softness", 3 100mm*100mm electrodes were cut, and the softness was measured 3 times under the conditions of slit width of 20mm and side head sinking of 8mm, and the average value was taken. The sum of the bending resistance of the sample itself and the maximum vector of the friction between the sample and the gap is called softness, expressed in millinewtons. The smaller the softness value, the softer the sample.

[0194] Whether the positive active layer contained in the positive electrode sheet is cracked or not: observe with naked eyes whether there are micro cracks or powder loss and light transmission. Determination of the severity of cracks: if there are no cracks, it is judged as "no crack"; if there are 1 to 2 cracks, it is judged as "micro cracks"; if there are 3 or more cracks, it is judged as "cracking"; if it is uncertain, re-coating can be considered for judgment. For better quantification, the surface density of the "crack-free" electrode sheet that is coated close to "micro cracks" is defined as the limiting surface density.

[0195] Lithium-ion battery cycle performance test method: charge and discharge range 4.0-2.0V; cycle three times at a rate of 0.1C, then cycle 1000 times at 1C to see the capacity retention rate.

[0196] The test results of the positive electrode sheets contained in the lithium-ion batteries of various embodiments are shown in Table 1 below.

[0197] Table 1

[0198]

[0199]

[0200] Comparing Examples B1, B3 and B4, it can be seen that when the degree of polymerization of the polymer polyether is 20 (Example B3), there are microcracks in the pole piece, and the pole piece softness and pole piece peeling strength are lower than those of samples with higher degrees of polymerization. With the increase of degree of polymerization, the flexibility of the pole piece is enhanced, and the anti-cracking effect is good. It is possible that with the increase of the degree of polymerization of the polymer, the number of single bonds increases and the steric hindrance effect is strengthened. At the same time, it is observed that when the degree of polymerization of the polyether is 30, the pole piece resistivity of the sample increases compared with the other two examples, indicating that the degree of polymerization of the polymer has an important influence on the comprehensive performance of composite dispersion.

[0201] Comparing Examples B1 and B2, and Comparative Example B3, it can be seen that -CO- and -CN- contained in the polymer can significantly reduce the viscosity of the slurry and improve the flexibility of the electrode, such as Example B1. In the presence of -CO- but without -CN-, such as Example B2, the viscosity of its sample is about 19% higher than that of Example B1, but its viscosity is significantly lower than that of Comparative Example B3. At the same time, the softness of the electrode in Example B2 is 602.55mN, which is 14 percentage points higher than that of Example B1. The flexibility is reduced relative to the flexibility of the electrode in Example B1, but it is still significantly better than Comparative Example B2. The electrode of Comparative Example B3, which does not contain -CO- and -CN- groups, has obvious cracking, and its softness is as high as 687.73mN, and the dispersion effect is poor. The slurry viscosity is increased by 67% compared with Example B1. In terms of electrochemical performance, its electrode resistivity is higher than the other two, and the cycle performance is greatly reduced.

[0202] Comparison of Example B1 with Comparative Example B1 and Comparative Example B3 shows that although the main chain still carries many -CO- and -CN- with high flexibility and excellent dispersibility, the influence of the side chain functional groups cannot be ignored. Although the main chain of the Comparative Example B1 sample contains -CO- and -CN- single bonds, the benzoic acid group of the side chain significantly increases the rigidity of the material. This is because the ring structure cannot undergo internal rotation, which is reflected in the significant increase in softness and the decrease in the peel strength of the electrode. In addition, the presence of -NO2 makes the material's dispersibility poor and the viscosity increases significantly.

[0203] Comparing Examples B1 and B5 and Comparative Example B2, it can be seen that as the symmetry of the side groups decreases, the viscosity of the sample slurry has no obvious change pattern, but at this time the dipole moment of the molecule is large, its flexibility will significantly decrease, and the cracking will gradually become more serious.

[0204] Comparing Examples B1 and B6, the dispersion and flexibility effect of directly compounding a polymer containing a symmetrical -CO- side group and another polymer containing a symmetrical -CN- side group is not as good as that of the chemically synthesized polymer. The slurry viscosity increased by 24.6% relative to the slurry viscosity in Example B1, and the pole piece softness value increased by 8.3%. Therefore, the dispersibility and flexibility of polymers whose main chains contain both -CN- and -CO- single bonds are better than the dispersibility and flexibility of polymers whose main chains contain only -CN- or -CO- single bonds. Further comparison of Examples B1 and B6 with Comparative Examples B2 to B3 shows that the slurry viscosity and pole piece flexibility of Examples B1 and B6 are significantly better than those of Comparative Examples B2 to B3. Therefore, when the main chain contains a single bond and the side chain is at least partially symmetrical, the dispersibility and flexibility of the polymer can be significantly improved.

[0205] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A dispersant, characterized in that: The invention comprises a polymer, wherein the main chain of the polymer contains at least one single bond group selected from -CO- and -CN-, and side chains are grafted onto the main chain, wherein the side chains are at least partially symmetrically connected to the main chain, and the side chains include at least one group selected from hydrocarbon groups, siloxane-containing segments and fat-containing segments.

2. The dispersant according to claim 1, characterized in that: The polymer includes repeating units A and / or repeating units B of different molecular structural formulas, and the main chain of at least one of the repeating units A and the repeating units B contains at least one single bond group of -CO- and -CN-; the general structural formula of the polymer includes the following general structural formula I: In the general structural formula I, 20≤a1≤50, 0≤a2≤45, 0≤a3≤50; the R1, R2, R3, R4, R5, and R6 independently contain any one of H, hydrocarbon groups, siloxane-containing segments, and fat-containing segments, wherein at least one pair of groups among R1 and R2, R3 and R4, and R5 and R6 are simultaneously any one of the hydrocarbon groups, siloxane-containing segments, and fat-containing segments; and / or The main chain contains single bond groups of -CO- and -CN-, and the molar ratio of -CO- to -CN- is (1 to 1.8):1; and / or The weight average molecular weight of the polymer is 200-6000.

3. The dispersant according to any one of claims 1 to 2, characterized in that The polymer comprises at least one of the repeating units shown in the following general structural formula I1, the repeating units shown in the following general structural formula I2, and the repeating units shown in the following general structural formula I3: Among them, 20≤a11≤50, 1≤a12≤5, 15≤a13≤45, 15≤a14≤40, 1≤a15≤8; R 11 , R 12 are independently any one of H, hydrocarbon, siloxane-containing segments and fat-containing segments, and the R 11 , R 12 Not at the same time H; R 13 is any one of H, hydrocarbon, siloxane-containing segment and fat-containing segment; R 14 , R 17 are independently any one of H and alkyl; R 15 , R 16 are independently any one of H, hydrocarbon, siloxane-containing segments and fat-containing segments, and the R 15 , R 16 Not at the same time H; R x1 , R x2 Separately And 1≤b1≤8.

4. The dispersant according to claim 3, characterized in that The polymer includes the repeating unit shown in the general structural formula I1 and the repeating unit shown in the general structural formula I3, and the general structural formula of the polymer includes the following general structural formula II: Among them, 0≤a11'≤50, 0≤a12'≤5; R 11’ , R 12’ are independently H, hydrocarbon, siloxane-containing segments and Any group in an aliphatic segment.

5. The dispersant according to any one of claims 1, 2 and 4, characterized in that The hydrocarbon group includes a C1-C8 straight-chain alkane group; and / or The fatty chain segment-containing group contains a fatty chain segment of C2 to C18; and / or The fatty chain segment-containing group includes at least one of a fatty alcohol group and a fatty ether group; and / or The siloxane segment-containing groups include groups shown in the following structural formula: Among them, 1≤c1≤4; R x3 , R x4 Separately And 1≤b2≤8; R y1 , R y2 Each is independently an alkyl group or an alkenyl group.

6. The dispersant according to claim 5, characterized in that The fatty alcohol group includes a group shown in the following structural formula: Among them, 2≤c2≤16, R y3 , R y4 are independently any one of H, alkane, ester group or silane group; and / or The fatty ether groups include the following groups: Among them, 2≤c3≤12, 2≤c4≤12, R y5 , R y6 , R y7 , R y8 Each is independently any one of H, an alkane group, an ester group or a silane group.

7. The dispersant according to any one of claims 1, 2, 4 and 6, characterized in that At least one end of the main chain of the polymer contains a functional end group, and the functional end group includes at least one of a nitrogen-containing group, a phosphorus-containing group, and -C(X)-, wherein X is a halogen substituent.

8. The dispersant according to claim 7, characterized in that The nitrogen-containing group includes at least one of -NH2 and -C≡N; and / or The phosphorus-containing group includes -H2PO3.

9. An electrode material, characterized in that: The invention comprises an electrode active material and a dispersant as claimed in any one of claims 1 to 8, wherein the electrode active material is a positive electrode active material or a negative electrode active material.

10. A battery comprising an electrode sheet and an electrolyte, characterized in that: The electrode sheet comprises the dispersant according to any one of claims 1 to 8 or the electrode material according to claim 9.